Systematic Literature Review: Analisis Penerapan E-Filling System dan Sanksi Pajak terdahap Kepatuhan Pelaporan SPT Tahunan Wajib Pajak Orang Pribadi (WPOP) - Fanny Kholifatul Nisa; Adis Salsabila; Dien Noviany R (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2024)
The government will make various efforts to increase tax revenue because taxes are a very large component of state revenue. These efforts include changing the tax collection system, improving tax laws, and implementing electronic tax reporting and payment. An application that aims to help wp fill out tax returns online called the e-filling system. Analyzing the implementation of the e-filling system in Indonesia is one of the objectives of this research. The method used in this research is Systematic Literature Review (LSR) where several journals published from 2019 to 2024 will be systematically analyzed. It is hoped that the results of this research will convey a better understanding of the clarity of the e-filling system in tax reporting SPT.